Increasing customer loyalty and WOM in an age of terror: Cross-cultural development and validation of the customers' reactions to terror scale (CRTS). (January 2022) - Gilboa, Shaked; Seger-Guttmann, Tali; Partouche-Sebban, Judith
Abstract: The threat of terror places customers in a vulnerable situation, giving rise to a variety of protective behaviors. The ability to employ these behaviors dictates customers' preferences for specific services. To enable a better understanding of this dynamic and its implications for positive customer outcomes, the current study developed a customers' reactions to terror scale (CRTS) in a four-stage process. Data were collected from customers in France and Israel across two service contexts, hospitality and public transportation. Nomological examinations showed that services that enable customers to employ protective behaviors under the threat of terror can facilitate increased loyalty and word of mouth (WOM).